CLUSTER WISE REGRESSION UNTUK IDENTIFIKASI HUBUNGAN IPM DENGAN APBD KABUPATEN/KOTA DI PROVINSI NTB - Siti Arni Wulandya; Wiwit Purwa Nurmayanti; Animar (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2020)
UNDP developed the Human Development Index (HDI) which is a measurement of the success of a region's development. HDIis an indicator that explains the ability of the population to be able to access development results in obtaining income, health,education and so on. Local governments carry out various strategies to improve the quality of human resources in their respectiveregions. One of the efforts of the local government to improve the quality of society in these various aspects is by allocating a bigenough funds in the regional expenditure budget (APBD). This study aims to identify the relationship between APBD and HDI indistricts and cities in the Nusa Tenggara Barat province. Using regression analysis, the relationship between the APBD and HDIof districts and cities in Nusa Tenggara Barat Province shows a negative correlation. On the other hand, different conclusionsare obtained when using the Cluster Wise Regression method. This method first classifies districts and cities based on their HDIvalues, then regression analysis is carried out separately for each existing group. Using this method, the relationship betweenAPBD and HDI of districts and cities in Nusa Tenggara Barat province shows a positive correlation.